EIB Global Report 2022/2023 - The impact - EUROPEAN INVESTMENT BANK (European Investment Bank, 2023)
Building on decades of experience working in Europe's neighbourhood, in Africa and around the world, under EU mandates and in support of EU policy priorities, EIB Global brings together all the financial, engineering and scientific expertise of the European Investment Bank to maximise impact. The new structure fosters strong, focused partnerships within Team Europe, with multilateral development banks and bilateral development agencies. With a stronger presence on the ground, it increases our cooperation with partner countries, clients, EU Member States and other development finance institutions. This publication reports on the first year of EIB Global. The first section reviews the development context, looking at global macroeconomic development and the different regions where EIB Global operates: EU neighbourhood countries sub-Saharan Africa the Western Balkans and Türkiye Asia and the Pacific, and Latin America and the Caribbean The report then turns to the overarching priorities of EIB Global and the European Fund for Sustainable Development Plus, examining investment needs and describing the response by EIB Global: Climate change Jobs and inclusive growth The Global Gateway The final part brings together all the information on the results and impact of EIB Global operations and the financial and non-financial contribution we make. It covers: How we measure results and impact Expected results of new projects EIB Global's contribution to new projects Evidence on the EIB's crowding-in effect Carbon footprint exercise Macroeconomic impact modelling Results of completed projects Lending volumes List of operations signed in 2022 A companion volume to this report, EIB Global Report: The Story [insert link], delves deeper into the rationale for, and experience gained from, individual EIB Global projects.